Hair style of Solanaceous plant: A morphological investigation - Das, Sagorika; Ganguly, Sudarshan; Das, Aurpi; Mukherjee, Debadrita; Ghosh, Srejoni; Biswas, Sayantika (Journal of Experimental Sciences, 2024)
Hairs are a covering of trichomes (fine hairs) covering plant surfaces including leaves, stems, fruits, sepals, petals and reproductive parts, and hold a significant position in plant taxonomy, physiology, stress response and fossil reconstruction study. To study the objective of hair morphology of Solanaceous plants, three local taxa - Solanum lycopersicum L., Physalis minima L., Solanum diphyllum L. were collected and epidermal hairs were investigated. Both vegetative and reproductive parts were prepared by following proper methodology including cleaning, peeling and observation under the light microscope. A total of ten different types of hairs have been documented in the tree taxa. The hairs can be classified as pointed gland, glandular hair, unicellular hair, unicellular stinging hair, multicellular stinging hair, multicellular finger hair, strigose, hirsute, hispid, and short conical hair. The similarities and dissimilarities of hair types among taxa can be used as a reference point for future systematic and stress response studies in the family Solanaceae.